2020
DOI: 10.3389/fonc.2020.01193
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Interval Dosing Strategy of Immune Checkpoint Inhibitors in Lung Cancer: Will it Outlast the COVID-19 Pandemic?

Abstract: Patients with lung cancer are particularly vulnerable to complications from coronavirus disease-2019 (COVID-19). Recurrent hospital visits and hospital admission are potential risk factors for acquiring infection with its causative pathogen, severe acute respiratory syndrome coronavirus−2 (SARS-CoV-2). As immune checkpoint inhibitors (ICIs) constitute the therapeutic backbone for the vast majority of patients with advanced lung cancer in the absence of actionable driver oncogenes, there have been intense discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…This is especially important to ensure prompt diagnosis and treatment of COVID-19 infections, thus preventing adverse outcomes in such patients. The decision to continue or suspend ICI treatment should be based on case-by-case approaches [ 44 , 50 ], where treatment adjustments may be performed to mitigate the risk of COVID-19 infection by reducing patients’ contacts to medical system, rather than due to ICI-related safety concerns. This is saliently important considering that cancer patients receiving active anticancer therapy may be at an increased COVID-19 infection risk due to frequent visits to hospitals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important to ensure prompt diagnosis and treatment of COVID-19 infections, thus preventing adverse outcomes in such patients. The decision to continue or suspend ICI treatment should be based on case-by-case approaches [ 44 , 50 ], where treatment adjustments may be performed to mitigate the risk of COVID-19 infection by reducing patients’ contacts to medical system, rather than due to ICI-related safety concerns. This is saliently important considering that cancer patients receiving active anticancer therapy may be at an increased COVID-19 infection risk due to frequent visits to hospitals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 30 95 104 We therefore agree with recently published consensus guidelines from the UK, 105 106 including continued use of front-line ICI therapies and to consider the approved alternative dosing regimens of either pembrolizumab 400 mg every 6 weeks as opposed to initial 3-week standard of care dosing per KEYNOTE-555 Cohort B data as well as nivolumab 480 mg every 4 weeks compared with every 2-week standard of care for those on nivolumab maintenance regimens. 107 …”
Section: Melanoma-specific Clinical Considerations Regarding Sars-cov-2 and Ici Usementioning
confidence: 99%
“…Third phase clinical trials CheckMate-066, -025, -057, and -017 showed similar PFS times and frequencies of side effects of 480 mg/kg Q4 W nivolumab dose compared to the standard scheme in patients after disease progression. Additionally, preliminary data from CheckMate-384 in pretreated patients with advanced-stage IIIB/IV NSCLC showed no signi cant differences between subgroups treated with 480 mg/kg Q4 W vs. 240 mg/kg Q2 W. The recorded adverse effect percentage was similar, with data from patients treated with 3 mg/kg Q3 W 29 . The more frequent use of lower doses might be more convenient for patients during the pandemic, according to cited research.…”
Section: Discussionmentioning
confidence: 63%